Fault-tolerant mhealth framework in telemedicine environment for chronic heart disease patients - Albahri, Ahmed Shihab Ahmed (Tanjong Malim, 2019)
Fault-tolerant mhealth framework in telemedicine environment for chronic heart disease patients by Albahri, Ahmed Shihab Ahmed